KETERKAITAN PENDIDIKAN KEWARGANEGARAAN DENGAN MATA PELAJARAN LAIN DALAM FAKTA SEJARAH - Nasution, Toni; Lu’Lu Rahmadanti; Melvi Sari Anggraini; Fadiah Dian Nashfati (PENDIS (Jurnal Pendidikan Ilmu Sosial), 2023)
Citizenship education plays a role in every educational institution in Indonesia, especially in tertiary institutions, namely that students are expected to have insight and national awareness and form a caring attitude towards others. Teaching materials for civic education applied in tertiary institutions are associated with other subjects such as religious education, Pancasila moral education, social education, and the history of the formation of Pancasila as the foundation of the state. the method used in collecting information in this article uses the method of literature analysis. With sources of information in the form of books and journals. From the results of this analysis it is expected that citizenship education will become a basic subject that must exist at every level of education in Indonesia, especially at tertiary institutions. So that future generations of the nation are not only good citizens, but also instill the meaning of Pancasila in their character, nature and deeds and are able to apply the values of citizenship in their daily lives, both in the social environment and in the learning environment in universities. In addition, citizenship education also functions to shape the character of students to become individuals who are democratic and virtuous and care for others in the life of the nation and state.